Pharmacogenetic interaction analysis of VEGFR-2 and IL-8 polymorphisms in advanced breast cancer patients treated with paclitaxel and bevacizumab. (December 2014) - Allegrini, Giacomo; Coltelli, Luigi; Orlandi, Paola; Fontana, Andrea; Camerini, Andrea; Ferro, Antonella; Cazzaniga, Marina; Casadei, Virginia; Lucchesi, Sara; Bona, Eleonora; Di Lieto, Marco; Pazzagli, Ilaria; et al.
Aim: To investigate pharmacogenetic interactions among VEGF-A, VEGFR-2, IL-8, HIF-1α, EPAS-1 and TSP-1 SNPs and their role on progression-free survival in a population of metastatic breast cancer patients treated with bevacizumab in combination with first-line paclitaxel.Patients & methods: Analyses were performed on germline DNA obtained from blood samples and SNPs were investigated by real-time polymerase chain reaction technique. The multifactor dimensionality reduction methodology was applied to investigate the interaction between SNPs.Results: One hundred and thirteen patients were enrolled from eight Italian Oncology Units (clinicaltrial.gov : NCT01935102). The multifactor dimensionality reduction software provided two pharmacogenetic interaction profiles consisting of the combination between specific VEGFR-2 rs11133360 and IL-8 rs4073 genotypes. The median progression-free survival was 14.1 months (95% CI: 11.4–16.8) and 10.2 months (95% CI: 8.8–11.5) for the favorable and the unfavorable genetic profile, respectively (HR: 0.44, 95% CI: 0.29–0.66, p < 0.0001).Conclusion: The pharmacogenetic statistical interaction between VEGFR-2 rs11133360 and IL-8 rs4073 genotypes may identify a population of patients with a better outcome.